AB0984 Development of a Juvenile Systemic Sclerosis Response Index (JSSRI). (9th June 2015) - Foeldvari, I.; Györgyi, Z.; Baildam, E.; Batu, E.D.; Blakley, M.; Cakan, M.; Curran, M.; Fligelstone, K.; Mouthon, L.; Nemcova, D.; Pilkington, C.; Ruperto, N.; et al.
Abstract : Background: Juvenile systemic sclerosis (jSSc) is an orphan disease. We have currently new promising effective medication to treat systemic sclerosis, but no valid outcome measures to assess the activity of the disease. Objectives: In the frame of the juvenile scleroderma working group of Paediatric Rheumatology European Society (PRES JSWG), we developed a provisional response index for jSSc. Methods: The facilitating committee designed a 3-round Delphi-exercise to obtain a core set of disease activity measures in jSSc. In Round 1, they were asked to add unique items in 21 preleminary domains. Round 2 judged the items' applicability and importance using a 1-10 scale. Previous respondents were asked to re-rate uncertain (score 4-7) items in Round 3. The aforementioned were followed by a face-to-face Nominal Group discussion to decide final items and domain structure. Results: 52 participants of Round 1 suggested a total of 131 items for the 21 domains. In round 2, 56 responders rated the significance of the items. The Nominal Group accepted 11 main domains for further validation containing 41 items (see table 1 ). Conclusions: We reached consensus and developed a Response Index, which should help to conduct clinical trials in jSSc. The validation of the JSSRI is planned in the frame of the Juvenile Scleroderma Inception Cohort. Disclosure of Interest: None declared